THE ROLE OF FETAL DEVELOPMENT MONITORING INDICATORS IN WOMEN WITH PREMATURE RUPTURE OF MEMBRANES (PROM) IN PROLONGING PREGNANCY - Babadjanova, G.S.; Karimova, Z.Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Premature rupture of fetal membranes continues to be a clinically important complication during pregnancy, affecting both maternal and neonatal outcomes. This article reviews up-to-date strategies for assessing and managing this condition, emphasizing the importance of a comprehensive evaluation that includes laboratory diagnostics, instrumental monitoring, and clinical judgment. The underlying causes—such as inflammatory processes, hormonal imbalances, oxidative damage, and mechanical stress—are analyzed. A tailored approach is highlighted as a key factor in optimizing perinatal results.